Unveiling the proteome of the fasting heart: Insights into HIF-1 pathway regulation - Benak, Daniel; Holzerova, Kristyna; Kolar, Frantisek; Chalupova, Miloslava; Hlavackova, Marketa (Frontiers in Physiology, 2024)
Fasting is a common dietary intervention known for its protective effects against metabolic and cardiovascular diseases. While its effects are mostly systemic, understanding tissue-specific changes in the heart is crucial for the identification of the mechanisms underlying fasting-induced cardioprotection. In this study, we performed a proteomic analysis of the fasting heart and attempted to clarify the molecular basis of fasting-induced cardioprotection. Our investigation identified a total of 4,652 proteins, with 127 exhibiting downregulation and 118 showing upregulation after fasting. Annotation analysis highlighted significant changes in processes such as lipid metabolism, the peroxisome pathway, and reactive oxygen species metabolism. Notably, the HIF-1 signaling pathway emerged as one of the focal points, with various HIF-1 targets exhibiting differential responses to fasting. Further experiments demonstrated downregulation of HIF-1α at both transcript and protein levels. Intriguingly, while gene expression of Egln3 decreased, its protein product PHD3 remained unaffected by fasting. The unchanged levels of pro-inflammatory cytokines indicated that the observed reduction in Hif1a expression did not stem from a decrease in basal inflammation. These findings underscore the complex regulation of the well-established cardioprotective HIF-1 signaling within the heart during 3-day fasting.